Conflict Management Styles: A Study of Organizational Politics among Professionals - MadihaYasin; Shazia Khalid (Journal of Political Studies, 2015)
One of the main outcome of organizational politics is organizational conflict which leads to other negative organizational behaviors. The aim of this study is to find the conflict management styles that are frequently used by the professionals working at various organizational hierarchies to reduce the conflicts to save the organizational environment. Moreover gender differences in using different conflict management styles were also explored. The sample comprised of one hundred professional teachers including lecturers, professors, associate professors and assistant professors. The ThomasKilmann Conflict Mode Instrument (Thomas and Kilmann, 1978) was used to measure different conflict management styles. The results of the present study revealed that the teachers mostly used the avoiding conflict management style. Moreover professors and associate professors used compromising conflict management style. But the assistant professor used the accommodating and lecturers used the avoiding conflict management style. Females more frequently use avoiding conflict management style than males. Seminars and workshops should be organized to train teachers using healthy conflict management styles; senior professors should adapt avoiding style more which can enhance work motivation of junior teachers.